Congenital bilateral aplasia of vas deferens (CBAVD): a reminder to clinicians - Koh, Peng Soon; Kuppusamy, Shanggar; Razack, Azad Hassan Abdul; Lee, G. (Faculty of Medicine, University of Malaya, 2008)
Male factor infertility which accounts for 30-50% of infertility is a major problem faced by married couples. Congenital absence of the vas deferens, though uncommon, remains the most common abnormality seen in extratesticular ductal and ejaculatory system, accounting for 1-2% of male infertility. It may be unilateral or bilateral. Association with renal abnormality has also been reported with congenital absence of vas deferens (1). The patients are asymptomatic and the congenital abnormality is usually detected when investigation for infertility is carried out. We present a case of an unusual presentation of congenital bilateral absence of vas deferens (CBAVD).